A model study by using polymeric molecular imprinting nanomaterials for removal of penicillin G - Kuru, Cansu Ilke; Ulucan, Fulden; Kusat, Keyser; Akgol, Sinan (SPRINGER, 2020)
We aimed to develop a molecularly imprinted polymeric systems with using penicillin G as a template molecule for removal of the antibiotic residues from environmental samples. Firstly, Pen-G-imprinted poly (2-hydroxyethyl methacrylate-N-methacryloyl-l-alanine) [p(HEMA-MAAL)] nanopolymers were synthesized by surfactant-free emulsion polymerization method. Then, template molecule (Pen-G) was extracted from nanopolymers. Synthesized nanopolymers were characterized by different methods such as Fourier-transform infrared spectroscopy (FTIR), elemental and zeta-size analysis, scanning electron microscope (SEM), and surface area calculations. Nanopolymers have 60.38 nm average size and 1034.22 m(2)/g specific surface area. System parameters on Pen-G adsorption onto Pen-G imprint nanopolymers were investigated at different conditions. The specific adsorption value (Q(max)) of molecularly impirinted p(HEMA-MAAL) nanopolymers was found 71.91 g/g for Pen-G in 5 mg/mL Pen-G initial concentration. Pen-G adsorption of molecularly imprinted nanopolymers was 15 times more than non-imprinted polymer. It is shown that obtained p(HEMA-MAAL) nanopolymer was a reuseable product which protected its adsorption capacity of 98.9% after 5th adsorption-desorption cycle. In conclusion, we suggest a method to develop a nanostructure, selective, low-cost molecularly imprinted polymeric systems with using penicillin G as a template molecule for removal of the antibiotic residues.
Keywords: Moleculer imprinted polymers; Nanopolymers; beta-Lactam antibiotics; Removal of penicillin G; SOLID-PHASE EXTRACTION; PERFORMANCE LIQUID-CHROMATOGRAPHY; MILK; ADSORPTION; NANOSPHERES; SORBENT; WATER; NANOPARTICLES; RECOGNITION; Environmental Sciences & Ecology